IMPLEMENTASI MODEL PEMBELAJARAN JIGSAW DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XDI SMA N 2 LUBUK SIKAPING - Yomita Afrina; Bambang Trisno; Irhamni (CV. ADIBA AISHA AMIRA, 2024)
This research was conducted to understand how the Jigsaw learning model and Islamic Religious Education learning are implemented at SMA N 2 Lubuk Suhuing, as well as what factors are applied and how they are implemented. The Jigsaw learning model is used in Islamic Religious Education at SMA N 2 Lubuk Sikaping. The research was conducted using a qualitative approach. Data collection techniques use observation, questionnaires and documentation. Based on the results of the research and analysis that has been carried out, it can be concluded that the Jigsaw learning model used has succeeded in making students become active participants in the class when studying Islamic religious education subjects at SMA N 2 Lubuk Suhuing, which includes first, the teacher divides the students into 5 After that, students were instructed to choose one leader from each member of the group. After that, the group leader took the questions that had been prepared by the teacher. After that, each member of the group discussed the topic that had been agreed upon by the teacher and each group discussed. After completing the discussion, each group member moves to another group to understand the next question, unless the group leader remains in his or her original group. secondly, students have to think in order to explain the meaning of the questions given by the teacher, after that each group returns to their original group to present the results they got. Supporting factors refer to all factors that play a role in, facilitate, support, smooth, support, help, speed up, and whatever happens in a particular situation. What is meant by inhibiting factors are all types of factors that have the property of inhibiting (making things slow), or more specifically, preventing and preventing something from happening. Another inhibiting factor is the duration of time, where this teaching model requires a longer period of time, but the application of this method needs to be aligned with the curriculum. Apart from that, students are included in a group that is less active because each individual accepted into the Expert Team group only makes small talk with the books they own. What is clear is that students only memorize and do not understand it, so that when they return to the group in general, the delivery is limited to reading the book again. Apart from the existence of supporting and inhibiting factors in the Jigsaw learning.